Sintesis dan Pemanfaatan Kitosan Berbasis Limbah Udang: Integrasi Etika Islam dan Sains dalam Pengembangan Bahan Ramah Lingkungan - Choiriyah, Ainur Rizqi; Madjid, Armeida D.R; Yulianti, Eny; Mubasyiroh, Mubasyiroh; Adi, Tri Kustono; Zulfikar, M. Ali; Setiyanto, Henry (Es-Syajar:Journal of Islam, Science and Technology Integration, 2025)
The increasing shrimp production and consumption in Indonesia generates significant amounts of shrimp shell waste, which has not been optimally utilized and often becomes an environmental problem. This waste is rich in chitin, which can be processed into chitosan—a multifunctional biopolymer with various applications in food, health, agriculture, and environmental fields. This literature review explores the synthesis process, characterization, and utilization of chitosan derived from shrimp shell waste, while highlighting the importance of integrating Islamic ethical values in the sustainable management of natural resources. The synthesis of chitosan involves demineralization, deproteinization, and deacetylation steps, with critical parameters such as temperature, time, and base concentration affecting the degree of deacetylation. The review shows that utilizing shrimp shell waste as a source of chitosan not only supports circular economy principles and waste reduction but also aligns with Islamic teachings on responsible environmental stewardship. The integration of science and Islamic ethics is expected to promote the development of high-value, sustainable, and environmentally friendly biomaterials.